Improving The Quality of Arabic Language Learning Through Artificial Intelligence at Junior High School Ma'arif Ngantru Tulungagung in The Era of Society 5.0 - Munir, Muhammad Syahrul; Sulayikho, Siti (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
The utilization of Artificial Intelligence (AI) in improving the quality of Arabic language learning at junior high school Ma'arif Ngantru Tulungagung in the era of Society 5.0 is an intriguing subject to be explored. Society 5.0 refers to a new paradigm where digital technology and humans interact harmoniously to create a sustainable and innovative society. The research methodology employed a qualitative approach, utilizing observation, interviews, and document analysis as data collection tools. The gathered data were analyzed using content analysis to identify patterns and trends in the implementation of AI in the context of Arabic language learning. The research findings indicate that the use of AI in Arabic language learning at junior high school Ma'arif Ngantru Tulungagung has significantly contributed to the improvement of the learning quality. AI is utilized to broaden the accessibility of Arabic language learning, enhance student engagement, and provide personalized and real-time feedback. Furthermore, AI is also employed to develop learning content tailored to individual needs and preferences. The implementation of AI in Arabic language learning at junior high school Ma'arif Ngantru Tulungagung also faces several challenges. These challenges include teacher training in utilizing AI technology, concerns regarding privacy and data security, and the management of infrastructure that supports AI requirements. In the context of the Society 5.0 era, this research provides an important contribution in demonstrating the potential of AI in enhancing the quality of Arabic language learning in junior high school.